Energy Loss in Condensed Matter of H1 and He4 in the energy Range 4<E<30 keV - Wijngaarden, Arie V. (My University, 1962)
Measurements are reported of the energy loss suffered by H1 and He4 particles, of 4-30 keV energy, in passing through thin films of carbon, aluminumoxide and VYNS. Only those particles that emerged in the forward direction were studied. Evidence is presented for identifying the stopping cross-sections per atom observed in this way with Se, the electronic component of the total stopping cross-section per atom. It appears that the calculated energy dependence of Se(∞√E) is somewhat in error, and that the magnitudes of these's for He4 are systematically too small by 10-15%.
Title: Energy Loss in Condensed Matter of H1 and He4 in the energy Range 4<E<30 keV, Author: Arie van Wijngaarden, Location: Thode